Frequência, intensidade e tendências nos eventos extremos de chuva em Ituiutaba/MG, no período de 1967 a 2019 - Freitas, Laiane Cristina de (2021)
The first decades of the 21st century evidenced a growing interest of climate scholars in quantifying and modeling the exact frequency of extreme rain events, starting from analyzes of increasingly extensive historical series, enabling periodic observations and monitoring of evidence of possible trends regarding the behavior of these events in the improvement of estimates in relation to projections, mainly due to the development of mechanisms that better suit the organization and management of the territory. Based on these premises, the research developed through this dissertation aimed to identify and analyze the frequency, intensity and trends in extreme rain events, starting from the temporal analysis of daily rainfall data in the period between 1967 and 2019 (comprising a historical series with 53 years of data), from the municipality of Ituiutaba located to the west of the state of Minas Gerais in the Southeast region, chosen after quantitative research that identified a considerable gap in studies carried out on this theme in the municipality. And, for a better dissertation on the central themes of the research, the construction of the theoretical framework was based on the approach of classic and contemporary bibliographies, especially those developed in the first decades of the 21st century, in which there was a significant increase in the development of studies on what they are and the genesis, consequences of their actions and attempts to estimate the periodicity of occurrences of extreme rain events. Thus, through the data used, it was possible to: analyze the dynamics of the city's rainfall regime; identify and categorize episodes of daily extreme events; quantify the variables of the magnitudes of Intensity-Duration-Frequency of intense rains, as well as compose an IDF Curve valid for the municipality; and, investigate possible indications of trends in the historical series, through the process of ranking and classifying these data. Therefore, the results indicated that when considering the usual behavior of rainfall in the municipality of Ituiutaba/MG, the distribution of rainfall shows a significant concentration in the months of October to March, which is the period of greatest occurrence of extreme rain events causing episodes that they range from Level I (small intensity) to Level IV (very large intensity), and by looking at how these events are temporally distributed in the return period of 2, 5, 10, 15, 25, 50, 75, 100 and 500 years, and duration of up to 24 hours and up to 1440 minutes, the relation of the variables of the IDF Curve was constituted, estimating how such extreme rain events evolve over the established years. And, finally, when investigating the trend factor considering the relationship between the rain variable (the central object analyzed) and the time variable (months and years that were analyzed), he identified the months of October and December show signs of trend variations and that should be plausible attention through the development of new research in the city of Ituiutaba/MG.